2008
DOI: 10.1159/000112221
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Work-Up of Pleural Effusions

Abstract: A wide range of diseases may be the cause of an accumulation of fluid in the pleural space. Pleural effusion is a major diagnostic problem, since the pleura is an inner cavity with no direct access. The aim of this review is to provide a practical approach to the investigation of the patient presenting with pleural effusion. This should help to accurately diagnose pleural effusion and keep time-consuming, but necessary, invasive investigations to the minimum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 154 publications
4
112
0
4
Order By: Relevance
“…Pleural effusions that are massive in amount and hemorrhagic or serosanguinous in character are likely to be malignant [7]. In our study, cytological examination of all pleural fluid samples that were bloody showed papillary structures of epithelial cells with or without psammoma bodies.…”
Section: Discussionmentioning
confidence: 45%
“…Pleural effusions that are massive in amount and hemorrhagic or serosanguinous in character are likely to be malignant [7]. In our study, cytological examination of all pleural fluid samples that were bloody showed papillary structures of epithelial cells with or without psammoma bodies.…”
Section: Discussionmentioning
confidence: 45%
“…Obtaining an upright lateral chest radiograph can further improve the detection of pleural effusions. On this view, 50 cc of fluid is the recognized volume that can be seen as blunting of the posterior costophrenic angle [1][2][3]. In contrast, ultrasound has been demonstrated to detect as little as 20 cc of pleural fluid [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…On this view, 50 cc of fluid is the recognized volume that can be seen as blunting of the posterior costophrenic angle [1][2][3]. In contrast, ultrasound has been demonstrated to detect as little as 20 cc of pleural fluid [2,4]. One study directly compared chest radiography to ultrasound for the diagnosis of pleural effusion, with the gold standard being computed tomography of the chest.…”
Section: Introductionmentioning
confidence: 99%
“…Pleural effusion was defined as an abnormal blunting of sharp lateral costophrenic angle on the chest posteroanterior view and a blunting of the sharp posterior costophrenic angle on the lateral radiography, 11 an echo-free (anechoic) space between the visceral and parietal pleura in ultraso nography, 12 and a sickle-shaped opacity in the most dependent part of the thorax posteriorly on chest computed tomography. 13 An ultrasonographic-guided thoracentesis was performed in all patients.…”
Section: Methodsmentioning
confidence: 99%